The influence of teachers' conceptions of teaching and learning on their technology acceptance. Issue 4 (19th May 2017) - Teo, Timothy; Zhou, Mingming
ABSTRACT: Prior research has attempted to incorporate different personal variables within extant theories of technology acceptance models (TAMs). This study further extends TAM by incorporating teachers' conceptions of teaching and learning (CoTL) in two forms: constructivist and traditional conceptions. The moderating effects of teachers' demographic variables including age, gender, teaching experience, teaching level, and technology experience were tested. Our findings demonstrated that incorporating CoTL could provide a richer and more nuanced understanding of technology acceptance, although no moderating effects on any demographic variables were found.